2010
DOI: 10.1104/pp.110.165431
|View full text |Cite
|
Sign up to set email alerts
|

mEosFP-Based Green-to-Red Photoconvertible Subcellular Probes for Plants  

Abstract: Photoconvertible fluorescent proteins (FPs) are recent additions to the biologists' toolbox for understanding the living cell. Like green fluorescent protein (GFP), monomeric EosFP is bright green in color but is efficiently photoconverted into a red fluorescent form using a mild violet-blue excitation. Here, we report mEosFP-based probes that localize to the cytosol, plasma membrane invaginations, endosomes, prevacuolar vesicles, vacuoles, the endoplasmic reticulum, Golgi bodies, mitochondria, peroxisomes, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(71 citation statements)
references
References 77 publications
(103 reference statements)
0
71
0
Order By: Relevance
“…Exchange of matrix-localized mito-mEosFP (Mathur et al, 2010) was analyzed between mitochondria in the leaves of 14-d-old Arabidopsis seedlings. Pieces of detached leaf were mounted in water between a slide and a coverslip on a chambered slide made from two parallel strips of ultrathin double-sided adhesive tape (Ekanayake et al, 2014).…”
Section: In Vivo Mitochondrial Fusion Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…Exchange of matrix-localized mito-mEosFP (Mathur et al, 2010) was analyzed between mitochondria in the leaves of 14-d-old Arabidopsis seedlings. Pieces of detached leaf were mounted in water between a slide and a coverslip on a chambered slide made from two parallel strips of ultrathin double-sided adhesive tape (Ekanayake et al, 2014).…”
Section: In Vivo Mitochondrial Fusion Assaymentioning
confidence: 99%
“…To test whether the increased rate of pulsing correlated with an increase in the extent of matrix mixing, and therefore intermitochondrial fusion, we devised a quantitative in vivo fusion assay using the mitochondriatargeted photoconvertible protein mito-monomeric (m)Eos (Mathur et al, 2010). Matrix-localized mEos was photoconverted within highly motile mitochondria in a region of leaf epidermis ( Fig.…”
Section: An In Vivo Fusion Assay Demonstrates That Matrix Mixing Is Imentioning
confidence: 99%
See 1 more Smart Citation
“…We generated a stable transgenic moss line constitutively expressing mitochondria-targeted mEOS (mtEOS; Mathur et al, 2010) and transiently transfected protoplasts of this line with an ER marker that comprises a signal peptide, mCerulean, and a C-terminal KDEL ER retention signal (spCerKDEL). We found that mitochondria in moss protoplasts were mostly small elongated tubular structures which move only at about a 10th of the speed of flowering plant mitochondria (max.…”
Section: Resultsmentioning
confidence: 99%
“…Mitochondria-targeted mEOS (Wiedenmann et al, 2004), containing the first 261 bp of the Nicotiana plumbaginifolia mitochondrial ATP2-1 coding sequence (X02868) as N-terminal targeting signal Mathur et al, 2010), was amplified via PCR (F ATAAGTCGACATGGCTTCTCGG AGGCTTCT, R ATCCGAGCTCTTATCGTCTGGCATTG) and ligated via the introduced SalI and SacI restriction sites into a newly assembled vector backbone containing the moss Actin5 promoter (Weise et al, 2006) and a NOS terminator, as well as homologous regions for gene targeting to the "P. patens targeting site 2" (PTA2; Kubo et al, 2013) locus (pAct5_PTA2). To assemble this vector, PTA2 5 ′ homologous region (F GCT CTTCTCCTGGGGATTAATTATTGGAGG, R GAAAGAACG AATTCGATCGGATCCGCGACTAGTGAGAGAATGTT) and PTA2 3 ′ homologous region (F CTAGTCGCGGATCCGAT CGAATTCGTTCTTTCTGTCATTAACTGG, R GCTCTTCAT TGTTCAGGATAATGGTTC) were amplified from genomic DNA, joined with two template PCR (Tian et al, 2004) and ligated into a pJET1.2 vector (Thermo Fisher Scientific).…”
Section: Cloningmentioning
confidence: 99%